PERSPECTIVES OF INCLUSIVE EDUCATION IN PAKISTAN: CONTENT ANALYSIS - Hanif, Saima; Fazil , Dr. Hina; Basri, Rabia; Hussain, Ghulam; Hanif, Saira; Naz, Tabssum (The journal of contemporary issues in business and government, 2022)
The study aimed at reviewing the research studies in the field of inclusive education in Pakistan with the purpose to identify different themes related to inclusive education. For this purpose, the researchers reviewed 16 research studies in the field of inclusive education in Pakistan. The content of these studies was analyzed by using thematic analysis technique.In this sense, the study was qualitative in nature following content analysis technique. The puipose of this content analysis was to summarize the research work carried by researchers on inclusive education at school level. To analyze the literature 16 researches were selected from national and international research journals during the period of 2010 to 2021. The findings of these researches were organized under six major themes and severa subthemesi.eTraces of Inclusive Education in Pakistan, Inclusive Education in Pakistan: Facts and Practice, Impediments, Issues and Challenges, Strengths of Inclusive Education in Pakistan, Mitigation Spaces. The content analysis revealed that that in Pakistan inclusive education is an emerging trend and is gaining momentum but slowly. A lot of work and reforms has to evolve for implementation of the inclusive education in Pakistan.